Resistência da madeira ao cisalhamento paralelo às fibras segundo as normas ABNT NBR 7190:1997 e ISO 13910:2005 - Matos, Gabriela da Silva [UNESP]; Molina, Julio Cesar [UNESP] (FapUNIFESP (SciELO), 2016)
Knowing the physical, and mechanical wood properties is essential for its proper destination and its final use. For the structural use, technical standards establish methodologies tests to determine the mechanical proper-ties. In Brazil, the standard for wooden structures [1] is currently under review. Part of the proposals for the revision version include the review of the mechanical properties tests methods. It has been noted that several specimens for the tests methods has been tested by the commission of CE studies - 02: 126.10 of the Brazili-an Technical Standards Association to determine the most representative model for the tests. Within this con-text, the aim of this study was to analyze the shear strength parallel to the grain using the current version of the Brazilian standard [1] and from the European standard [2]. The simplified relationship between shear strength and compression parallel to the grain (fv0,k/fc0) proposed by the Brazilian standard [1] was studied as well. This study considered specimens of Pinus elliottii and Eucalyptus saligna. The results showed that the Brazilian standard had higher values for shear strength than the European standard. The differences in the shear strength parallel to the grain between Eucalyptus saligna and Pinus elliottii considering the two stand-ards were approximately 35% and 65%, respectively, and the simplified relationship (fv0,k/fc0,k) obtained for the eucalipto was that most agree with the values proposed by the Brazilian standard [1].
Shear strength of wood in direction parallel to the grain according to the standards abnt nbr 7190:1997 and iso 13910:2005
Keywords: Shear; Standardization; Strength